ENVIRON - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
A new, computerized data base of the Tropical Development and Research Institute (TDRI) has been given the cryptic name ENVIRON. It can be used as a clearinghouse for information on the effects of pesticides on tropical environments: toxicity...